2018
DOI: 10.3389/fneur.2018.00656
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ARHGAP26 Autoantibodies Are Associated With Isolated Cognitive Impairment

Abstract: Autoantibodies against the RhoGTPase-activating protein 26 (ARHGAP26) were originally identified in the context of subacute autoimmune cerebellar ataxia. Further studies identified a wider clinical spectrum including psychotic, affective, and cognitive symptoms. Only a few patients reported so far had evidence of a tumor association. A prospective analysis between January 2015 and December 2017 at the Dept. of Neurology at Charité—Universitätsmedizin Berlin identified 14 patients with ARHGAP26 autoantibodies o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…Two of these patients, as well as another patient without ACA, had signs of possible limbic encephalitis [ 13 ], indicating that the spectrum of neurological manifestations associated with ARHGAP26-IgG/anti-Ca may be broader than originally thought. In three further cases, isolated cognitive decline was noted [ 1 ]. In addition, 17 further ARHGAP26/anti-Ca-positive patients were reported by the Mayo Clinic in 2020, 15 of whom had subacute progressive cerebellar ataxia and 2 peripheral neuropathy [ 15 ], and several as yet unpublished additional cases were identified in our laboratories over the subsequent years.…”
Section: Introductionmentioning
confidence: 99%
“…Two of these patients, as well as another patient without ACA, had signs of possible limbic encephalitis [ 13 ], indicating that the spectrum of neurological manifestations associated with ARHGAP26-IgG/anti-Ca may be broader than originally thought. In three further cases, isolated cognitive decline was noted [ 1 ]. In addition, 17 further ARHGAP26/anti-Ca-positive patients were reported by the Mayo Clinic in 2020, 15 of whom had subacute progressive cerebellar ataxia and 2 peripheral neuropathy [ 15 ], and several as yet unpublished additional cases were identified in our laboratories over the subsequent years.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, antibodies against ARHGAP26 were first discovered in patients with subacute cerebellar ataxia [33,34]. Subsequent studies have shown that these antibodies are related to cognitive impairment and dyslexia [35][36][37][38]. Interestingly, researchers also detected other systemic tumors in patients with such neurological diseases who were positive for ARHGAP26 antibodies, suggesting that anti-ARHGAP26 antibodies may be a potential tumor predictor in such patients [38,39].…”
Section: Arhgap26 In Glioblastomamentioning
confidence: 99%
“…Neurological manifestations in decreasing order of frequency included the following: gait ataxia (gait, 7, limb 4), dysarthria (5), nystagmus (5), dizziness (3), cognitive impairment (3), depression (3), hyperkplexia (2), ocular flutter (1), oscillopsia (1), and recurrent psychoses (1). Half of the patients had a tumor, including ovarian cancer (1), breast cancer (1), melanoma (1), B cell lymphoma (1) prostate adenocarcinoma (1), and gastric adenocarcinoma (1), suggesting that this is a paraneoplastic antibody biomarker 1–6 . Here we describe the clinical and oncological associations of an additional 14 GRAF1–IgG‐seropositive patients.…”
mentioning
confidence: 92%
“…Immunoglobulin‐G (IgG) autoantibodies specific for ρ GTPase activating protein 26 (ARHGAP26, also known as GTPase regulator associated with focal adhesion kinase [GRAF1]) have been reported in 10 patients to date 1–6 . Neurological manifestations in decreasing order of frequency included the following: gait ataxia (gait, 7, limb 4), dysarthria (5), nystagmus (5), dizziness (3), cognitive impairment (3), depression (3), hyperkplexia (2), ocular flutter (1), oscillopsia (1), and recurrent psychoses (1).…”
mentioning
confidence: 99%